INFLUENCE OF BUDI BICARA (DISCRETIONARY VIRTUE) IN STRATEGIC PLANNING OF BUSINESS ENTERPRISES - Suhaimi Mhd Sarif; Dolhadi Zainudin (Journal of Islamic Management Studies, 2022)
Influence of Budi Bicara or discretionary virtue is essential in organizations. The use Budi bicara in the Malay Muslim intellectualism manifests intellectual empathy and caring through teamwork for sustainable performance. Budi in Malay term is defined as mind and bicara is defined as conversational discourse. Business owners applied Budi Bicara in strategic planning and business activities. The process requires conversational discourse and intellectual participation with empathy, sharing and caring. This chapter explores the application of budi bicara in formulating vision, mission and objectives.